Atypical employment: legal protections for atypical/non-standard employees in Malaysia / Nazruzila Razniza Mohd Nadzri - Mohd Nadzri, Nazruzila Razniza (2014)
Atypical employment or non-standard employment is seen as a common trend opted by employers in engaging employees nowadays. Non-standard employment takes in form of fixed-term contract relationship, part-time working, temporary work and agency working. This form of employment is becoming increasingly important particularly in Malaysia as it offers flexibility for employers in accommodating the organization demand. Meanwhile, it promotes uncertainty in term of job security and other legal protections of employees. Subsequently, this paper is intended to identify the fundamental features of atypical employment and reflects on the legal protection offers to these non-standard employees. The relevant statutory provisions and case laws will be analysed to figure out the extent the labour laws in Malaysia regulate atypical employments and finally confer the readers with the suggestions of improvement and/or alternative legal framework.